Pengaruh Literasi Keuangan Dan Financial Technology Terhadap Inklusi Keuangan Mahasiswa STAI Tasikmalya ( Studi Pada Mahasiswa Program Studi Ekonomi Syariah Tahun Akademik 2017-2021) - Mardani, Dede Aji; Abduh, Muhammad (MASHLAHAH, 2022)
This study aims to determine the effect of financial literacy and financial technology on financial inclusion of students of Islamic economics study program STAI Tasikmalaya. This research is quantitative and the research data used are primary and secondary data. The population in this study was 159 students of the Islamic economics study program at STAI Tasikmalaya for the 2017-2021 academic year. The sampling technique used was the proportional sampling method, so that 50 students of the Islamic economics study program STAI Tasikmalaya were obtained to be respondents. The analytical method used is descriptive analysis and multiple linear regression analysis. The data were statistically processed using the t-test and F-test models. The results of this study indicate that partially the variables of financial literacy and financial technology have a positive and significant effect on Islamic financial inclusion for students of the Islamic economics study program STAI Tasikmalaya. financial literacy and financial technology variables simultaneously have a significant effect on the financial inclusion of students of the Islamic economics study program STAI Tasikmalaya. It is proven by the results of the analysis of the coefficient of determination where financial literacy and financial technology variables affect the financial inclusion of students of the Islamic economics study program STAI Tasikmalaya by 65.7% and the remaining 34.3% is influenced by other variables not mentioned in this study.